The approach to headache in Primary Health Care by medical professionals - Freitas, Naiana Queiroz de; Nogueira, Guilherme Nobre; Araújo, Marisa Bezerra de; Passos, Pedro Robson Costa; Filho, Luciano Barbosa de Sousa Santos; Sousa, Ana Letícia Gurgel Sampaio de; Santos, Raquel Capistrano Dos; Banhatto, Gabriel Machado de Souza Lima; Fiuza, Priscila Barbosa Tabuso; Sousa, Bruno Henrique Alcântara Lopes de; Lima, Hanna Lopes; Lima, Larissa Chaves; et al. (Headache Medicine, 2023)
Full abstract in PDF.